Interrelation of Income, Inflation and Aggregate Demand in the Russian Economy - Ilyashenko, Vladimir Vladimirovich; Kuklina, Lyudmila Nikolaevna (Economy of Regions, 2018)
The choice of economic policy instruments to ensure economic growth is one of the important problems of the country, The purpose of the article is to analyze and characterize the interconnection of income, inflation and aggregate demand in the Russian economy and at the regional level in order to increase the effectiveness of the state’s economic policy, We show the contradictory causes of demand-pull inflation and cost-push inflation, as well as anti-inflationary measures aimed at overcoming them, The hypothesis is that the decline in inflation results from tight monetary policy and the use of monetary measures, The decline in inflation have negative effect associated with a reduction in aggregate demand in the economy, a slowdown in economic development or decline in production, a decrease in investment and innovation activity in the country, a decrease in real incomes, Based on the analysis of tabulated models, we have determined functional dependencies between changes in household incomes, inflation and aggregate demand, We have revealed that there was no unambiguous correlation between the money incomes of the population, investments, government spending and changes in the level of inflation in Russia, Moreover, the increase in total spending was more often accompanied by a decrease in inflation than by the development of inflation processes, We have concluded that the transition to the state policy of stimulation of cumulative demand is appropriate, The results of the research can be used when developing the state economic policy and regional programs aimed at ensuring the economic development of territorial subjects of the Russian Federation